An Unusual Case of Medial Dislocation of the Subtalar Joint with Fracture of the Talar Body (Journal of Pakistan Orthopaedic Association, 2019)
Talus dislocation with a fracture of the body of talus is a relatively rare clinical entity. Medial subtalar dislocation accompanying this type of fracture was reported only once in Germany in 1968. For the past 50 years, there have been no other cases in the literature. In this article, we report the results of surgical treatment and 2-year follow-up of a patient who presented to the emergency department with such an injury. Radiographs of the ankle revealed a subtalar medial dislocation; however, a talus fracture was not detected. An Xray in the lateral projection of the right ankle obtained after closed reduction under sedative anesthesia showed a fracture of the talar body with displacement. Under spinal anesthesia with anteromedial and anterolateral exposure to the ankle joint, fracture was openly reduced and fixed two cannulated screws(4.5 mm)n the day of presentation to support subtalar joint stability, and one 2-mm Kirshner wire was placed toward the calcaneus to the talus. At 2-year follow-up excellent functional outcome of ankle joint was noted without any avascular necrosis of talus or tibiotalar and subtalar arthrosis.